Does Size Matter? Knowledge-Based Development of Second-Order City-Regions in Finland. - Yigitcanlar, Tan; Inkinen, Tommi; Makkonen, Teemu (Taylor & Francis, 2015)
Achieving knowledge-based urban development (KBUD) depends profoundly on not only encouraging the development of economic activities, but also strengthening the societal, environmental and governance bases of city-regions. However, there is a knowledge gap in understanding how KBUD works in the second-order city-region (SOCR) context. This warrants more attention as SOCRs potentially help secure balanced development and territorial cohesion. This paper aims to empirically investigate KBUD performances of SOCRs in order to generate new insights. An assessment framework is utilised in the Finnish context, where the findings provide a nationally benchmarked snapshot of the degree of achievements of SOCRs based on numerous KBUD performance areas. The results shed light on the unique Finnish urban and regional development process, and provide lessions for other SOCRs.
Keywords: Regionalplanung; Regionalentwicklung; Stadtregion; Stadtentwicklung; Regionalanalyse